Capital Market Development, ICT Adoption, and Sustainable Growth of MSMEs in Nigeria: An ARDL Approach - Aisha Abdulaziz; Sudha Mavuri; Jamiu Adeniyi Yusuf; Agus Arwani; Happy Sista Devy (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines the impact of capital market development and information and communication technology (ICT) adoption on the growth and sustainable development of Micro, Small, and Medium Enterprises (MSMEs) in Nigeria within the framework of the Sustainable Development Goals (SDGs). Given the critical role of MSMEs in employment creation, income generation, and inclusive economic growth, the study investigates whether capital market deepening and digital transformation significantly enhance enterprise performance and long-term viability. Using the Securities and Exchange Commission (SEC) as an institutional reference, the analysis employs the Autoregressive Distributed Lag (ARDL) cointegration approach to estimate both long-run and short-run relationships among market capitalization, ICT penetration, financial inclusion, inflation, and MSME output. The empirical findings confirm the existence of a stable long-run relationship among the variables. Capital market development exerts a positive and statistically significant effect on MSME growth, indicating that improved access to market-based financing supports enterprise expansion and productivity. ICT adoption also demonstrates a strong and significant positive impact, highlighting the role of digital technologies in enhancing operational efficiency, market access, and competitiveness. However, sustainable development indicators exhibit mixed effects on MSME outcomes, suggesting a misalignment between macro-level SDG implementation strategies and enterprise-level realities. Overall, the results underscore the importance of strengthening ICT infrastructure, deepening capital market accessibility, and promoting inclusive financial systems to enhance MSME resilience and ensure their long-term contribution to sustainable economic growth in Nigeria